AN ANALYSIS OF THE STUDENTS’ DIFFICULTY IN READING THE TOEFL PREDICTION TEST - Tira Nur Fitria (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2022)
The objective of this study is to know the students’ difficulty TOEFL prediction test of reading skills. This study uses qualitative research. The findings show some difficulties faced by the students in reading TOEFL. In external factors, they are: 1) Using the reading technique of skimming to find the main idea or point of the reading as a whole. 2) Using techniques of scanning to find more specific information from a long reading in the reading. 3) Reading the questions first then reading the reading on the TOEFL reading. 4) Feeling the topic of the TOEFL reading passages is less or unfamiliar. 5) Feeling the reading passages on the TOEFL reading is too long or too much. 6) Feeling lots of unfamiliar vocabulary in the TOEFL reading. 7) Feeling the number of TOEFL reading questions is too much. 8) Feeling the amount of time to do the TOEFL reading questions is short because of only about 55-60 minutes. While, in internal factors, the students: 1) Having limited memory when reading the TOEFL’s passages. 2) Tending to choose easy questions first than difficult questions. 3) Having a lack of concentration in doing the TOEFL reading test. 4) Having previous experience taking the TOEFL reading test before. 5) Having a lack of practice in reading TOEFL passages. 6) Having boredom when doing TOEFL reading questions. 7) Feeling easily distracted by other things when reading TOEFL reading questions. 8) Being busy interpreting each word/sentence while reading the TOEFL passages.